Improving access and flow within Child and Adolescent Mental Health Services: a collaborative learning system approach - Marco Aurelio; Amar Shah; Jamie Stafford (BMJ Open Quality)
Long waiting times for Child and Adolescent Mental Health Services (CAMHS) have been linked to poorer outcomes for those seeking care. CAMHS teams in England have seen recent increases in referrals, resulting in challenging waiting times nationally. Although recent health policy has brought an increase in funding and staffing, it is believed that only 25% of those needing care receive it. Between trusts, there is considerable variation in waiting times, leaving many waiting longer than others waiting for care. East London Foundation Trust has been seen to have higher waiting times for CAMHS than other organisations across the country between June 2017 and September 2018, seven CAMHS teams were supported to use quality improvement (QI) as part of a collaborative learning system with the aim of improving access and flow. Each team was encouraged to understand their system using basic demand and capacity modelling alongside process mapping. From this teams created project aims, driver diagrams and used Plan Do Study Act cycles to test changes iteratively. Measurement and data were displayed on control charts to help teams learn from changes. Teams were brought together to help learn from each other and accelerate change through a facilitated collaborative learning system. Of the seven teams that began the collaborative learning system, six completed a project. Across the collaborative learning system collectively there were improvements in average waiting times for first, second and third appointments, and an improvement in the number of appointments cancelled. For the individual teams involved, three saw an improvement in their project outcome measures, two just saw improvements in their process measures and one did not see an improvement in any measure. In addition to service improvements, teams used the process to learn more about their pathway, engage with service users and staff, build QI capability and learn together.